2017
DOI: 10.3233/jad-161114
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Tau Association with Brain Atrophy in Mild Cognitive Impairment and Alzheimer’s Disease

Abstract: Abstract.Background: Peripheral (plasma) and central (cerebrospinal fluid, CSF) measures of tau are higher in Alzheimer's disease (AD) relative to prodromal stages and controls. While elevated CSF tau concentrations have been shown to be associated with lower grey matter density (GMD) in AD-specific regions, this correlation has yet to be examined for plasma in a large study. Objective: Determine the neuroanatomical correlates of plasma tau using voxel-based analysis. Methods: Cross-sectional data for 508 ADNI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 18 publications
3
42
1
2
Order By: Relevance
“…Moreover, plasma tTau levels were correlated with neither CSF tTau nor CSF pTau181 levels. Former studies have shown diagnostic value of plasma tTau, but only at the stage of full‐blown dementia 35, 36, 37, 38, 39. Thus far, no studies have focused on nondemented individuals only.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, plasma tTau levels were correlated with neither CSF tTau nor CSF pTau181 levels. Former studies have shown diagnostic value of plasma tTau, but only at the stage of full‐blown dementia 35, 36, 37, 38, 39. Thus far, no studies have focused on nondemented individuals only.…”
Section: Discussionmentioning
confidence: 99%
“…After aspiration, approximately 10 ml of CSF was deposited into a polypropylene transfer tube and frozen at -80 • C. Aliquots were shipped to the University of Pennsylvania for batch analysis of t-tau, p-tau 181 , and Aβ 1−42 . Methods of CSF biomarker analysis of t-tau, p-tau 181 , and Aβ 1−42 are described elsewhere (Shaw et al, 2009;Grossman et al, 2014;Deters et al, 2017;Alosco et al, 2018c). Concentrations of these analytes served as outcomes for markers of neurodegeneration (t-tau), hyperphosphorylated tau (p-tau 181 ), and amyloidosis (Aβ 1−42 ).…”
Section: Csf Analytesmentioning
confidence: 99%
“…The amount and spatial distribution of abnormal tau, seen pathologically as neurofibrillary tangles in brain, is closely related to the onset of cognitive decline and the progression of AD. The identification of morphological phenotypes of tau on in vivo neuroimaging may help to differentiate mild cognitive impairment (MCI) and AD from cognitively normal older adults (CN) and provide insights regarding disease mechanisms and patterns of progression [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%